I Know It Is Not Real (And That Matters) Media Awareness vs. Presence in a Parallel Processing Account of the VR Experience - Hartmann, Tilo; Hofer, Matthias (Frontiers in Virtual Reality, 2022)
Inspired by the widely recognized idea that in VR/XR, not only presence but also encountered plausibility is relevant (Slater, Phil. Trans. R. Soc. B, 2009, 364 (1535), 3549–3557), we propose a general psychological parallel processing account to explain users’ VR and XR experience. The model adopts a broad psychological view by building on interdisciplinary literature on the dualistic nature of perceiving and experiencing (mediated) representations. It proposes that perceptual sensations like presence are paralleled by users’ belief that “this is not really happening,” which we refer to as media awareness. We review the developmental underpinnings of basic media awareness, and argue that it is triggered in users’ conscious exposure to VR/XR. During exposure, the salience of media awareness can vary dynamically due to factors like encountered sensory and semantic (in)consistencies. Our account sketches media awareness and presence as two parallel processes that together define a situation as a media exposure situation. We also review potential joint effects on subsequent psychological and behavioral responses that characterize the user experience in VR/XR. We conclude the article with a programmatic outlook on testable assumptions and open questions for future research.